Handling of Actors of Criminal Acts of Terrorism in the Protection of Human Rights - Huda, Khoiril (Universitas Negeri Semarang, 2017)
Criminal acts of terrorism, for Indonesia, have become a very real threat and are of particular concern to the government. The formation of Densun 88 Anti-Terror, according to the establishment of the National Counterterrorism Agency (BNPT), shows that the government is really serious about dealing with this problem. Various acts of terrorism in Indonesia from time to time continue to experience changes in motives and actors and even target segmentation. However, in many cases, the unclear procedure for handling perpetrators or suspected terrorism still creates a lot of controversy. Starting from the protection of human rights and the principle of the presumption of innocence, to how laws and regulations provide clear rules on how and how human rights are protected in the handling of terrorism cases.